Gambaran Kemandirian Personal Hygiene Anak Usia Sekolah di SD Negeri 1 Gianyar - Ni Wayan Astri Savitri (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Children at the elementary school level are in a phase of rapid growth, encompassing intellectual, physical, and social development. Within the age range of 6–12 years, children are expected to begin managing their own self-care, including maintaining daily personal hygiene. Personal hygiene refers to a set of self-care practices performed to maintain physical health and psychological well-being. Independence in personal hygiene can be defined as a child’s ability to carry out personal hygiene activities independently without reliance on others, related to both physical cleanliness and psychological comfort. This study aimed to describe the level of personal hygiene independence among school-age children at SD Negeri 1 Gianyar. The research employed a quantitative descriptive design with a cross-sectional approach. The study population consisted of 376 students from grades I to III, with a sample of 194 students selected using proportionate stratified random sampling. The results showed that the majority of respondents demonstrated good independence in personal hygiene, with 186 children (95.9%) categorized as independent, while 8 children (4.1%) were categorized as moderately independent. Children’s independence tended to increase with age, and no significant differences were found between male and female students. These findings indicate that the role of families and schools, through consistent habituation and support, plays a crucial role in fostering children’s independence in maintaining personal hygiene.